(3aj GdEYdGe GdJLGQj hGdeaGhVGJ GdJLGQjI GdOhdjIs - (3NGdU UGaj(B, (3UGdMs ((3GdLRGFQ(B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2000)
(3eaghe GdEYdGe(B- (3GdeYdheGJ GdJLGQjI Mhd Shb GdeDSSI(B- (3GdeYdheGJ GdeJYdbI HGdeTJQjf(B- (3GdeYdheGJ GdeJYdbI HGdSdY hGdefJLGJ hGdHVGFY(B- (3JUfja GdeYdheGJ GdJLGQjI(B- (3eUGOQ GdeYdheGJ(B.s
Keywords: (3GdEYdGes; (3GdEYdGe GdJLGQjs; (3GdJLGQI GdOhdjIs